Testing of The Gold’s Role as a Safe Haven and Hedge for Sharia Stocks in Indonesia - Robiyanto, R. (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
Gold as a commodity, since ancient time, is always viewed as a safe haven asset. This study tested the function of gold as a safe haven and hedge for sharia stocks in Indonesia. Data used in this study are a monthly closing of Jakarta Islamic Index (JII) on Indonesia Stock Exchange and monthly closing price of gold in the international market during May 2008 until September 2017. Data analysis was done by using OLS and QREG. The result of this study is gold can serve as a hedge for sharia stocks in Indonesia during the research period. The study further found that when extreme shocks occur in the Indonesian stock market, gold can serve as a safe haven asset for sharia stocks in Indonesia. Investor suggested shifting their assets into gold to secure their investment when stock market conditions experience a drastic decline.DOI: 10.15408/aiq.v10i2.6527